2009
DOI: 10.1002/jcc.21265
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the prion protein based on the fragment molecular orbital method

Abstract: We performed fragment molecular orbital (FMO) calculations to examine the molecular interactions between the prion protein (PrP) and GN8, which is a potential curative agent for prion diseases. This study has the following novel aspects: we introduced the counterpoise method into the FMO scheme to eliminate the basis set superposition error and examined the influence of geometrical fluctuation on the interaction energies, thereby enabling rigorous analysis of the molecular interaction between PrP and GN8. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
108
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 53 publications
7
108
0
Order By: Relevance
“…15,22 Our calculations showed that the L2-α2 region with weak interactions in the neutral pH was considerably destabilized under mild acidic pH condition, although the structural stability of the L2-L4 region with strong attractive interaction in the neutral pH model did not alter considerably in the mild acidic pH ( Table 3 and Fig. 2).…”
Section: It Has Been Suggested That Prpmentioning
confidence: 82%
See 4 more Smart Citations
“…15,22 Our calculations showed that the L2-α2 region with weak interactions in the neutral pH was considerably destabilized under mild acidic pH condition, although the structural stability of the L2-L4 region with strong attractive interaction in the neutral pH model did not alter considerably in the mild acidic pH ( Table 3 and Fig. 2).…”
Section: It Has Been Suggested That Prpmentioning
confidence: 82%
“…Although the FMO calculations at the MP2 level can provide quantitative information on the molecular interactions between the residues in a protein, [12][13][14][15] such an analysis based on individual interactions involves enormous computational complexity; for example, PrP129-224, which contains ∼100 residues, could have more than 5,000 molecular interaction energies for residue pairs. Conversion of the intramolecular interactions between residues into those for secondary structure elements or pairs dramatically reduces the computational complexity and eases the interpretation of the calculation results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations